Profitability Analysis and Sensitivity Level of White Shrimp (Litopenaeus vannamei) Cultivation Using the Millennial Shrimp Farming (MSF) System - Pramudia, Zulkisam; Kurniawan, Andi; Prayogo, Tri Budi; Amin, Abd Aziz; Dwi, Yogita Ayu; Susanti, Susanti; Al Zamzami, Ilham Misbakudin; Moehammad, Khibar Syiar (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2024)
Millennial Shrimp Farming (MSF) is an innovative cultivation system known for its efficient production methods and advanced technology. This study explores the economics aspects of cultivating vaname shrimp using MSF systems, with a focus on profitability and sensitivity. This research was carried out at the MSF CV Nusantara Agro Mandiri, using three cultivation ponds and one water reservoir. To assess business viability, the analysis carried out includes Total Cost, Total Revenue, R/C, Profit, BEP Unit, BEP Sales, PP, and ROI. The results indicate that this business is economically feasible, with a BEP Unit of 1,186 kg and a minimum BEP sales price of IDR42,279/kg, while the production reached 6,120 kg. The R/C value of 1.30 signifies efficiency and profitability. The business vulnerability, at 30%, exceeds the Indonesian state bank interest rate of 12%. With an ROI of 30% and a NPV of IDR382,662,975, along with Net B/C, R/C, IRR, and PP indicators (6.96; 1.3; 63%; and 1.6 years, respectively), this business can be classified as both feasible and profitable. In sensitivity analysis, white shrimp farming with the MSF system is a viable and profitable endeavor with a low level of sensitivity to fluctuations in feed prices and uncertain operational revenues.